A new insight on the diffusion growth mechanism of intermetallic compounds in Al-Er system. (December 2022) - Tang, Zhichao; Cui, Jin; Yu, Muzhi; Zhu, Weiqiang; Xu, Zhengbing; Zeng, Jianmin; Xu, Tao; Yang, Haodong; Tan, Yapeng; Yang, Bo
Graphical abstract: Highlights: During annealing, the growth characteristics of Al-Er intermetallic compounds are accord with layer-terraced growth. In Al-Er system, AlEr grows by consuming Er component, the growth of Al3 Er proceeds by swallowing AlEr. The pre-exponential factor and activation energy of the Al3 Er are 7.126 × 10 −8 m 2 ·s −1 and (88.4 ± 5.3) kJ·mol −1 respectively. Al-Er diffusion couples were successfully prepared by casting cladding in the atmosphere. Abstract: The diffusion growth of intermetallic compounds in Al-Er alloys are closely related to the properties of the alloys. The current work aims at explaining the dominance of Al3 Er in the Al-Er alloys precipitation phases and the interface thin layer phenomenon by diffusion couple technique, estimating the parabolic growth constant and diffusion activation energy of intermetallic compound in Al-Er diffusion couples to provide theoretical guidance for the design of new Al-Er alloys. In this work, Al-Er diffusion couples were successfully prepared by casting-cladding method in the atmosphere. The growth of Al-Er intermetallic compounds at diffusion couple interface during annealing were observed and recorded by High-Temperature Laser-Scanning Confocal Microscopy at 673, 698, 723 and 748 K respectively. The results show that the growth characteristics of Al-Er intermetallic compounds were accord with layer-terraced growth during annealing. The thickness of intermetallic compound was linear with the square root of time at experimental temperature. The intermetallic compound layer was composed of Al3 Er and a very thin AlEr phase. The parabolic growth constants of Al3 Er phase at 673, 698, 723 and 748 K were 1.017 × 10 −14, 1.609 × 10 −14, 3.111 × 10 −14 and 4.76 × 10 −14 respectively. The activation energy of Al3 Er phase was (88.4 ± 5.3) kJ/mol and the pre-exponential factor was 7.126 × 10 −8 m 2 /s.